2021
DOI: 10.1093/eurjpc/zwab200
|View full text |Cite
|
Sign up to set email alerts
|

Addressing disparities of care in non-ST-segment elevation myocardial infarction patients without standard modifiable risk factors: insights from a nationwide cohort study

Abstract: Aims The importance of standard modifiable cardiovascular risk factors (SMuRFs) in preventing non-ST-segment elevation myocardial infarction (NSTEMI) is established. However, NSTEMI may present in the absence of SMuRFs, and little is known about their outcomes. Methods and results We analysed 176 083 adult (≥18 years) hospitalizations with NSTEMI using data from the United Kingdom (UK) Myocardial Infarction National Audit Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Interestingly, Figtree et al showed that the events contributing to higher all-cause mortality in SMuRF-less patients occurred in the first 30 days; yet allcause mortality remained increased in the SMuRF-less group at a 8-year patient follow-up (7). Nevertheless, a recent study presented discordant outcomes demonstrating that SMuRFless patients with NSTEMI had lower in-hospital rates of cardiovascular mortality and major adverse events than patients with (9). It has been proposed that this discordance might be due to the underlying etiology of NSTEMI or due to the possible enrollment of patients with milder subclinical forms of SMuRFs across the continuum of SMuRF risk (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Figtree et al showed that the events contributing to higher all-cause mortality in SMuRF-less patients occurred in the first 30 days; yet allcause mortality remained increased in the SMuRF-less group at a 8-year patient follow-up (7). Nevertheless, a recent study presented discordant outcomes demonstrating that SMuRFless patients with NSTEMI had lower in-hospital rates of cardiovascular mortality and major adverse events than patients with (9). It has been proposed that this discordance might be due to the underlying etiology of NSTEMI or due to the possible enrollment of patients with milder subclinical forms of SMuRFs across the continuum of SMuRF risk (25).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of SMuRF-less patients seems to be rising during the last two decades and has been reported to be up to 20% (5). Recent studies have also investigated the prognostic impact of the SMuRF-less status on the clinical course of ACS, yielding contradictory data on patients' short-and long-term survival (5)(6)(7)9). Nevertheless, differences in intrinsic characteristics of the ACS and especially in coronary angiographic characteristics in SMuRF-less patients, as compared to the general ACS patient population, have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…34 For example, the rDANCAMI score could be used to risk-stratify different subpopulations with AMI with less common co-morbidities in everyday practice. 35,36 Finally, it encourages cardiovascular clinicians to consider crossspecialty input to optimize non-cardiovascular risk factors as a potential means to improve AMI outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…STEMI also found to be associated with obesity and male gender and younger individuals al these results are in accordance with results of this study. 14,15 Risk factors are studied in this study on younger individuals of single tertiary care center in Islamabad, for better generalizability study can be conducted in multiple study settings across the country or regions and on a larger sample size. Study concluded that more male young adults were found to be having a STEMI, this could be because more male ratio of patients.…”
Section: Discussionmentioning
confidence: 99%